Professor Nikolai Alekseevich Bogoraz (1874–1952) - M. A. Polishchuk; S. Yu. Borovets; S. H. Al-Shukri (Вестник хирургии имени И.И. Грекова)
This article contains historical aspects of the life of the great Russian scientist and surgeon – Nikolai Alekseevich Bogoraz. The work is devoted to the scientific discoveries of Nikolai Alekseevich in the field of urology, operative surgery, as well as the main points of the biography of N. A. Bogoraz are described here: the path from a student of the Military Medical Academy to an outstanding Russian surgeon. Nikolai Alekseevich was born on February 1 (13 according to the Julian calendar), 1874 in the city of Taganrog, Donskoy Army region – modern Rostov region. The future famous scientist and surgeon, Nikolai Alekseevich, graduated with a gold medal at first from the Tiflis Gymnasium in 1892, and then from the Military Medical Academy in 1897, graduating with the degree of «doctor with honors». Further, N. A. Bogoraz had a long, multidisciplinary professional path. In 1920, Nikolai Alekseevich lost both lower limbs because of a traffic accident, which gives a halo of heroism to the image of the professor. However, this tragic accident did not hindered the talented surgeon from creating a monumental work that glorified N. A. Bogoraz in the world medical community, – «Reconstructive surgery» in two volumes. N. A. Bogoraz died at the age of 78 on July 15, 1952 from repeated myocardial infarction and was buried at the Vvedenskoye cemetery in Moscow.